2022
DOI: 10.3390/en15072495
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Decision Support System for Modeling Transport and Passenger Flows in Human-Centric Urban Transport Systems

Abstract: Engineering human-centric urban transport systems should be carried out using information technology in forecasting traffic and passenger flows. One of the most important objects of urban transport systems’ progress is modeling patterns of transport flows and their distribution on the road network. These patterns are determined by the subjective choice of city residents of traffic routes using public and private transport. This study aimed to form a sequence of stages of modeling transport and passenger flows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
1
0
3
Order By: Relevance
“…Відповідно до [6,9] моделі транспортної логістики поділяються на: моделі транспортних систем; моделі попиту на транспортне обслуговування та імітаційні моделі.…”
Section: теоретичні основи дослідженняunclassified
See 2 more Smart Citations
“…Відповідно до [6,9] моделі транспортної логістики поділяються на: моделі транспортних систем; моделі попиту на транспортне обслуговування та імітаційні моделі.…”
Section: теоретичні основи дослідженняunclassified
“…Відповідно до [6] під моделлю розуміють штучний об'єкт, який відображає з певним ступенем точності основні властивості досліджуваного об'єкта-оригіналу. Модель має відмінну форму від її реального об'єкта і служить засобом пояснення механізму функціонування системи і її вдосконалення.…”
Section: результатиunclassified
See 1 more Smart Citation
“…The allocation and planning of urban basic charging service facilities present a comprehensive challenge, involving multi-source data and complex scenarios. With the growing adoption of deep learning (DL) methods, research findings in time series forecasting have found extensive applications across diverse domains, including demand forecasting [43], stock trend forecasting in financial markets [44], power load forecasting [45], traffic flow forecasting [46], energy consumption forecasting [47], and more. Statistical-based time series prediction methods are commonly employed for linear time series modeling; however, real-world research reveals nonlinear characteristics within these time series.…”
Section: Introductionmentioning
confidence: 99%
“…But this algorithm is pri marily focused on data protection rather than data control. Davidich, et al [12] analyzes the modeling of traffic and pas senger flows in urban transport systems for an intelligent deci sion support system. The relevance analysis here relies on the comparison of data flows, which is not always possible for other transport systems.…”
Section: Introductionmentioning
confidence: 99%